Inventory positioning and optimization of global supply chain - Muhammad Aadil Dafir. (2010)
Companies today need to maintain efficient operations management and a lean supply chain management to remain competitive. Gone are the days when manufacturers could stockpile large quantities of raw materials, load-up with work-in-process; and pack warehouses with finished goods. These ways cost too much, require too much working capital, and contribute to inconsistent and longer lead times. Cash unnecessarily tied up in inventory could be better spent elsewhere such as product development, expanded marketing and sales, reengineering, expansion, acquisitions and also debt reduction. Inventory positioning is important as well. Expanding to areas with cheaper labour offers the possibility of radical cost reductions. However, exploiting the promise of low-cost sourcing requires rethinking supply chain strategy. With the benefits are risks and hidden costs that some only discovered after making significant investments. However, with proper research and strategic planning, expanding various functions globally will reap long term benefits. For this study, we posit that for a global company to remain competitive as it expands in the prospective wind energy industry, it has to constantly maintain a streamline global supply chain and a strategically planned inventory positioning system. We address the problem of inventory management. Subsequently, we touch on inventory positioning by determining the supply chain nodes and subsequently investigate where inventory should be held to minimize holding costs given a pre-specified order fill rate. We propose a suitable inventory positioning approach for Suzlon.